PENERAPAN MODEL PEMBELAJARAN DEBAT AKTIF DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SDN 1 SUKARAME DAN SDN 1 SUKALAKSANA KABUPATEN CIANJUR - Asep Suryana; Fitriyani Kosasih; Eliva Sukma Cipta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of the active debate learning model in improving elementary school students' critical thinking skills at SDN 1 Sukarame and SDN 1 Sukalaksana, Cianjur Regency. The research employed a qualitative approach using a case study method to obtain an in-depth understanding of the learning process and its impact on students' critical thinking abilities. The research participants consisted of school principals, fifth-grade teachers, and students selected purposively based on their direct involvement in the learning activities. Data were collected through classroom observations, semi-structured interviews, and documentation. The validity of the data was ensured through source triangulation, technique triangulation, and member checking, while data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings indicate that the implementation of the active debate learning model creates a more interactive, student-centered, and collaborative learning environment. Students demonstrated significant improvement in expressing logical arguments, analyzing problems, evaluating different opinions, and drawing evidence-based conclusions. The implementation was supported by teachers' readiness, school support, and students' enthusiasm, although challenges such as limited instructional time and differences in students' confidence were identified. Overall, the active debate learning model proved effective in fostering students' critical thinking skills and promoting active participation in classroom learning, making it a valuable instructional strategy for elementary education.